TiO2/ZnS/GO Composites and Beads : A Dynamic Triad with Enhanced Adsorption and Photocatalytic Performance - Devagi, Kanakaraju; Allysha Riziana, Reduan; Ying, Chin Lim (Springer Nature, 2024)
Ternary composites, featuring TiO2 as a key component, have gained recognition for their exceptional photocatalytic performance in water treatment. In this study, we investigated the effectiveness of TiO2/ZnS/GO composites, both in powdered and immobilized forms, for the removal of single and mixed dye pollutants, including methylene blue (MB), methyl orange(MO), and Rhodamine B (RhoB). Comprehensive characterizations utilizing various spectroscopic and microscopic techniques confirmed the successful fabrication of TiO2/ ZnS/GO composites. The findings revealed that the composite achieved impressive individual removal rates of 98.4%, 83.6%, and 95.7% for MB, MO and RhoB, respectively, through adsorption and photocatalytic effects. In the case of co-existing dyes, the composite eliminated 99.1%, 44.3%, and 62.1% of MB, MO and RhoB, respectively. Furthermore, when incorporated into alginate, TiO2/ ZnS/GO–CaAlg beads displayed exceptional dye adsorption capacity and facilitated easy recovery from the reaction medium. This engineered TiO2/ ZnS/GO composite exhibits significant potential in both its powdered and bead forms, particularly due to its superior adsorption capabilities compared to its photocatalytic effects. These findings offer valuable insights into its prospective application in wastewater treatment, with a key emphasis on its efficiency in simultaneously tackling multiple pollutants.